Cebuano cultural identities: prospects for a culturally responsive pedagogy - Inocian, Reynaldo B.; Callangan, Annie Lorrie I.; Medrano, Darleen R.; Gualiza, Windelee G. (Journal of Research, Policy & Practice of Teachers and Teacher Education, 2020)
This study described the Cebuano cultural identities and prospects in search of a culture-based instruction model. This sought to find out the linguistic varieties of the Cebuano speakers; contrast the differences and similarities in the inasal making process; and identify the variations in the celebrations of festivals in Cebu. This study utilized a case study design with 15 research participants from the three selected cluster locations. These Cebuano cultural identities vary according to geographic location and other socio-historical factors.  Clipping and borrowing of words and expressions, from adjacent islands and roots of the colonial past, are indicative of these factors of language variations. The practices of inasal making are based on inherited traditions of the place such as variations on the use of logistics and needed ingredients to embellish the entire corpus of a sanitized butchered pig before its roasting. Towns and cities celebrate festivals in thanksgiving of their patron saint – a symbolism of their religious and cultural traditions. These varied cultural orientations support the argument to establish a cultural grounding on instructional initiatives in the Asian context. The findings juxtapose the exploration of Inasal Teaching Model (ITM) as a localized and a contextualized teaching model that serves as a nexus in various phases of instruction, for quality teaching in the field of culture-based education.